Balance of coastal and marine assets for Panggang Island and Semak Daun Island, Kepulauan Seribu DKI Jakarta - Yudi Wahyudin; Mahipal; Dudi Lesmana; Muhammad Yuusuf Wahyudin; Muhammad Nur Hussein Wahyudin (JURNAL MINA SAINS, 2023)
Coastal and marine areas hold great wealth for the welfare of coastal and small island communities with dynamic magnitudes. Panggang Island and Semak Daun Island have the potential for promising coastal and marine resource assets and provide benefits for community welfare. The research aims to compile a balance sheet of coastal and marine resource assets for Panggang Island and Semak Daun Island. The research was conducted in the Seribu Islands Administrative District, DKI Jakarta Province, in August-September 2023. It included various information data to map the value of ecosystem services and asset balances. The economic valuation method using the benefits transfer technique is used as input for the value of natural resource assets and the coastal and marine environment. The research results show that the value of coastal and marine resource assets of Panggang Island and Semak Daun Island have quite significant dynamics. In 2014-2019, the coastal and marine resource assets of Panggang Island and Semak Daun Island experienced a considerable decline, namely 1,001.92 billion ( Panggang Island ) and 59.97 billion ( Semak Daun Island ). They decreased respectively by 200.38 billion per year (12.34%) and decreased by 11.99 billion/year (9.29%). The estimation results show that there will be an improvement in asset value in 2022 for Panggang Island to 687.73 billion and for Semak Daun Island to 82.32 billion. The estimation results show that there has been an improvement in the ecosystem during the 2020-2022 period. This increase is due to reduced pressure on coastal and marine ecosystems on the two islands. Ecosystem-based integrated management needs to be carried out so that the sustainability and value of resource assets can benefit the welfare of coastal and small island communities.